KARAKTERISTIK KONDISI LINGKUNGAN, JUMLAH STOMATA, MORFOMETRI, ALANG-ALANG YANG TUMBUH DI DAERAH PADANG TERBUKA DI KABUPATEN BLORA DAN UNGARAN - Fujiyanto, Zelly; Prihastanti, Erma; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Reed is a grass that grows wild, widespread in the forests, fields, gardens and other open environments. The public generally considers thatÂ it's weeds for agricultural land, but many industry companies utilize reeds for the purposes of drug raw materials, syrups and health drinks. Reed requires an open environment with high light intensity and a fertile soil for growth. Environmental conditions in Blora has a high light intensity and in Ungaran district has fertile soil, so that the differences in the environment can affect the quality of the reeds. The purpose of this study to know the environmental conditions, the number of stomata, morphometry of reeds. The design used was Completely Random Design by a single factor, namely the place of sampling in the area open fields in Blora and Ungaran. Sampling of each region performed 10 replication. Analysis of the data used is T test at significant level of 95% and 99%. Parameters observed that environmental conditions, the number of stomata, morphometry, the results showed that Blora has a light intensity and a higher temperature, humidity and precipitation lower than in the District Ungaran plant reeds in Blora has an average number of stomata less than in the area of plant Ungaran.The growth of reeds in Blora lower than the high reeds in Ungaran. Similarly, the thickness of the leaves of reeds in Blora thinner than the thick leaves of reeds in the area Ungaran. Reed rhizome in Blora slightly longer and a diameter longer than in Ungaran. Â Keywords : Environmental condition, morphometry